Epidemiology of Shiga toxin-producing Escherichia coli in the bovine reservoir: seasonal prevalence and geographic distribution - Dewsbury, Diana Marisa Adele (Kansas State University, 2015)
Cattle shed Shiga toxin-producing Escherichia coli (STEC) in their feces. Therefore, cattle pose a risk to contaminate produce, water, and beef products intended for human consumption. The United States Department of Agriculture Food Safety and Inspection Service consider seven STEC serogroups (O26, O45, O103, O111, O121, O145, and O157) as adulterants in raw, non-intact beef products. Contrary to O157, the frequency and distribution of non-O157 serogroups and virulence genes have not been well-established in cattle. Therefore, the objectives of my thesis research were: 1) to appraise and synthesize data from peer-reviewed literature on non-O157 serogroup and virulence gene prevalence, and 2) to determine the prevalence of seven STEC in feedlot cattle feces across seasons. A systematic review and meta-analysis of published literature were conducted to gather, summarize, and interpret the existent data regarding non-O157 serogroup and virulence gene prevalence in cattle. Random-effects meta-analyses were used to obtain pooled non-O157 fecal prevalence estimates for continents worldwide and meta-regression analyses were conducted to evaluate effects of specific factors on between-study heterogeneity. Results indicated that non-O157 serogroup and virulence gene fecal prevalence significantly differed (P < 0.05) by geographic region, with North America yielding the highest pooled prevalence estimate worldwide. While previous research has demonstrated a strong seasonal shedding pattern of STEC O157, data regarding the seasonality of non-O157 STEC shedding in cattle is very limited. A repeated cross-sectional study was conducted to obtain serogroup and virulence gene prevalence data for the seven STEC in pre-harvest cattle feces, in summer and winter. We found that non-O157 serogroups were recovered in fecal samples collected in both seasons but virulence genes, thus STEC, were rarely detected in summer and undetected in winter. In conclusion, non-O157 STEC are present in cattle feces at very low frequencies, but STEC O103 and O157 significantly differed (P < 0.05) between seasons. Overall, the research described in this thesis greatly contributes to the limited body of data regarding non-O157 serogroup and virulence gene distribution in cattle and provides a better understanding of two major risk factors, season and geographic distribution, associated with STEC fecal shedding in cattle.
Keywords: Escherichia coli; Cattle; Shiga toxin; PrevalenceSTEC; Veterinary Medicine (0778)